A study on the effect of durio zibethinus-based surfactant on crude oil for enhanced oil recovery (EOR) application / Mohd Zakaria Khamis. - Khamis, Mohd Zakaria (2009)
Experimental works to study the effect of Durio Zibethinus- based surfactant on crude oil were carried out. This surfactant, Lecithin is extracted from the durian rinds using Supercritical fluid extraction. In this experiment, four tests have been done to analysis the physical and chemical properties of the surfactants. The equipment use is Fourier transforms infrared spectroscopy (FTIR), Gas chromatography- Mass spectrometry (GC-MS), X-ray Diffraction (XRD) and Du Nouy Tensiometer. The experimental analysis has been conducted to identify the chemical compound that contain in the surfactant. After that, the analysis of the physical properties conducted to measure the interfacial tension between crude oil and water for EOR application. This work has proved that the chemicals can be produced locally using local source, consequently posing a potential in EOR processes.